ANALISIS PENGETAHUAN REMAJA PUTR ANALISIS PENGETAHUAN REMAJA PUTRI TERHADAP PERILAKU HYGINE MENSTRUASI REMAJA PUTRI: STUDI KASUS PADA SMP DESA SUDAJI SINGARAJA: ANALISIS PENGETAHUAN REMAJA PUTRI TERHADAP PERILAKU HYGINE MENSTRUASI REMAJA PUTRI: STUDI KASUS PADA SMP DESA SUDAJI SINGARAJA (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2020)
Every normal teenage girl experiences menstruation every month marked by the discharge of blood from the genitals. If menstruation does not maintain menstrual hygiene, it can cause the entry and development of phatogenic bacteria which can cause reproductive problems. The study was conducted to determine the knowledge of young women on menstrual hygiene behavior at SMP Desa Sudaji, Singaraja. This type of research is a cross-sectional design and data analysis techniques using the Wilcoxon test to determine the relationship between knowledge of young women on menstrual hygiene behavior in young women. Based on the results of the study showed significant results with p values ​​of 0.037 and p 0.000, which proved that there was a significant relationship between these variables.